Pengaruh Aktivitas Sepeda Terhadap Kesehatan Dan Pola Hidup Masyarakat Kecamatan Blora Ditengah Pandemi Covid-19 (Indonesian Journal for Physical Education and Sport, 2022)
To maintain health and fitness during this Covid-19 pandemic, people are advised to exercise a lot. Cycling is a physical activity that can be done independently. The current bicycle trend is a unique phenomenon to be studied more deeply in order to find out its health benefits. This study uses a survey research method conducted in Blora District with a total sample of 100 residents. Data collection techniques were carried out by filling out a healthy lifestyle questionnaire from the GPAQ and collecting weight and height data on residents who did cycling activities to measure BMI. Then for data analysis using SPSS software. The results showed that the correlation between cycling activity and health had a significance value of 0.313 > 0.05. The test results show the significance of the cycling activity variable and the application of a healthy lifestyle with a significance value of 0.535 > 0.05. Based on the results of the study showed that there was no significant relationship between cycling activity and the application of a healthy lifestyle. In conclusion, physical activity does not affect health variables and the application of a healthy lifestyle. The researcher's advice from the results of the study is that people who have cycling physical activity with less intensity are expected to increase their physical activity through other activities. This is because physical activity has many health benefits during a pandemic like now